In-situ probing of the Fischer-Tropsch reaction on Co single crystal surfaces up to 1 bar - Patrick Lömker; David Degerman; Christopher M. Goodwin; Mikhail Shipilin; Peter Amann; Gabriel L. S. Rodrigues; Fernando Garcia-Martinez; Raffael Rameshan; Jörgen Gladh; Hsin-Yi Wang; Markus Soldemo; Alexander Holm; et al. (Nature Communications)
Abstract The surface chemistry of the Fischer-Tropsch catalytic reaction over Co has still several unknows. Here, we report an in-situ X-ray photoelectron spectroscopy study of Co $$\left(0001\right)$$ 0001 and Co( $$10\bar{1}4$$ 10 1 ¯ 4 ), and in-situ high energy surface X-ray diffraction of Co $$\left(0001\right),$$ 0001 , during the Fischer-Tropsch reaction at 0.15 bar - 1 bar and 406 K - 548 K in a H2/CO gas mixture. We find that these Co surfaces remain metallic under all conditions and that the coverage of chemisorbed species ranges from 0.4–1.7 monolayers depending on pressure and temperature. The adsorbates include CO on-top, C/-CxHy and various longer hydrocarbon molecules, indicating a rate-limiting direct CO dissociation pathway and that only hydrocarbon species participate in the chain growth. The accumulation of hydrocarbon species points to the termination step being rate-limiting also. Furthermore, we demonstrate that the intermediate surface species are highly dynamic, appearing and disappearing with time delays after rapid changes in the reactants’ composition.